Technological and Economic Substantiation for Efficiency of Involvement in the Processing of Complex Reserves of Coal Deposits - SHULYATIEVA, Liudmila I. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).19, 2017)
The technique of grounding the involvement in mining of coal reserves with complex conditions of occurrence taking into account the reduction of specific capital investments for construction of new horizons of existing and new mines. The algorithm of estimation of influence of factors that complicate the testing of stocks and affect their production. The method of evaluation of the carrying value of opening and preparing the mine workings. The proposed approach allows the subsoil user to choose the most effective design solution, taking into account the degree of involvement in processing of complex inventory, but the investor – is to assess the feasibility of participation in specific investment project.